2017
DOI: 10.3197/096327117x14847335385599
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Value Types and Environmental Behaviour in Four Countries: Universalism, Benevolence, Conformity and Biospheric Values Revisited

Abstract: Using the social-psychological literature on the antecedents of environmental behaviour and comparative data from Germany, India, Israel and South Korea, we test four value types that correspond with environmental behaviour. Our cross-national context represents varying social, economic, cultural and environmental configurations, giving credence to the effects of values. The authors collected survey data among students on a variety of environmental behaviours and on questions that comprise Schwartz's value sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 60 publications
2
68
0
1
Order By: Relevance
“…Doing good for others can also be motivated by human values. Benevolence, as a value, has implications for environmental behavior (Katz et al 2017). It is a form of kindness in social living.…”
Section: Discussionmentioning
confidence: 99%
“…Doing good for others can also be motivated by human values. Benevolence, as a value, has implications for environmental behavior (Katz et al 2017). It is a form of kindness in social living.…”
Section: Discussionmentioning
confidence: 99%
“…A number of researchers have found that environmental concern has a significant influence on travel mode decisions [54,55]. Numerous transportation factors influence environmental concern including apparent threats of environmental destruction to the society, individual, or the earth [56][57][58][59]; concerned responsibility or emotional state of guiltiness for the environmental problem; willingness in the reduction of car use for decreasing the environmental problem [60]; perceived benefits and barriers to sustainable travel behavior [61]. Therefore, based on the above literature, the proposed hypothesis can be as follows: Hypothesis 3.…”
Section: Environmental Concern and Acceptability To Sustainable Transmentioning
confidence: 99%
“…It has been argued that industry can achieve CE through five phases— take , make , distribute , use , and recover , that is, converting their linear business processes ( take , make , and distribute ) to circular (Prieto‐Sandoval, Jaca, & Ormazabal, ). CE is a concept widely studied in China and the European Union (EU), the adoption of the latter driven by legislation, but there is a big scope for analysis beyond those countries (Katz‐Gerro, Greenspan, Handy, & Lee, ; Zhu et al, ). Moreover, although there is research in larger organisations (Kumar, Sezersan, Garza‐Reyes, Gonzalez, & Al‐Shboul, ; Zhu et al, ), study on SMEs adoption of CE is scant.…”
Section: Introductionmentioning
confidence: 99%